2020
DOI: 10.1088/1755-1315/548/8/082071
|View full text |Cite
|
Sign up to set email alerts
|

Use of vegetable and fruit powder in the production technology of functional food snacks

Abstract: The article provides information on the development of formulations and production technology of functional food snacks (bars, tablets, cubes) from vegetables, fruit and secondary raw materials from the production of direct-pressed fruit and vegetable juices for a healthy snack during the day (morning, afternoon, evening) in accordance with the current trend of nutrition: “The right products at the right time”. In a balanced diet, a person needs two to three snacks during the day between main meals. Each snack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The World Health Organisation recommends a dietary fibre intake of at least 25 g per day, including 3 g ß-glucans. The loss of biologically active substances can be reduced by using effective technological methods (Perfilova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation recommends a dietary fibre intake of at least 25 g per day, including 3 g ß-glucans. The loss of biologically active substances can be reduced by using effective technological methods (Perfilova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Powder was perceived as an ingredient for desserts or pastries and as a sweetener for hot drinks or yoghurt. In a recent review about the influences of dried fruit and vegetable powder on cake quality, Perfilova et al [24] reported that the powder of fruits and vegetables exhibited benefits in attracting consumers by improving the appearance, texture, nutritional values, sensorial properties and shelf life of cakes. Specifically for persimmon powder, Hosseininejad et al [10] reported that its addition acted as a functional ingredient to glutenfree muffins.…”
Section: Consumption Contexts For Fresh Fruit and Productsmentioning
confidence: 99%
“…15,16 These ingredients often composed of whole spinach or fractions are suitable for use in dietary supplements as well as in functional or nutritional food products. 17,18 Interest in powdered ingredients is often driven by their long shelf life, low cost of transportation, sensory properties and diverse product applications. However, unlike traditional fruit and vegetable products, phytochemical stability, density, and nutrient/phytochemical bioavailability are often not characterized across ingredient platforms.…”
Section: Introductionmentioning
confidence: 99%